Assessment of RANK/RANK-L prevalence and clinical significance in NSCLC European Thoracic Oncology Platform Lungscape cohort and SPLENDOUR randomized clinical trial. (January 2023) - Peters, Solange; Letovanec, Igor; Mauer, Murielle; Dafni, Urania; Ejedepang, Dunson; Biernat, Wojciech; Bubendorf, Lukas; Warth, Arne; Pokharel, Saraswati; Reinmuth, Niels; Majem Tarruella, Margarita; Casas-Martin, Jose; et al.
Highlights: RANK expression was determined in a retrospective cohort of resected NSCLC and in a prospective cohort of advanced NSCLC. The prevalence of RANK expression was 50% in adenocarcinoma and 12% in squamous cell carcinoma. RANK and RANK-L positivity was seen in 35% and 5%, respectively, in the pretrial biopsies. At the prespecified expression level of 1%, no prognostic or predictive effect could be found. Abstract: Background: The primary objective of this study is to evaluate the clinical significance of RANK/L expression, in both a retrospective cohort of surgically resected stage I-III NSCLC (Lungscape) and a randomized clinical trial-cohort (SPLENDOUR) of advanced NSCLC treated with chemotherapy alone or in combination with denosumab. Methods: RANK-L expression was assessed on tissue microarrays (TMAs) in Lungscape and whole sections in SPLENDOUR, using immunohistochemistry, with H-scores values > 0 indicating positivity. Prevalence of RANK positivity and its association with clinicopathological characteristics, and patient outcome was explored in a subset of the ETOP Lungscape cohort and in SPLENDOUR. Also investigated were the prevalence of RANK overexpression (proportion of positive cancer cells ≥ 50%) in the Lungscape cohort, and RANK-L in the SPLENDOUR trial. Results: In the Lungscape cohort, RANK expression was assessed at a median follow-up of 46 months (N = 488 patients; 4 centers); 35% were female, 44/49/6% adenocarcinomas (AC)/squamous cell carcinomas (SCC)/other, 48/27/25% with stage I/II/III. Median RFS/TTR/OS were 58/Not reached/74 months. Prevalence of RANK expression was 31% (95%CI:27%–35%); significantly higher in AC: 50% (95%CI:43%–57%) vs SCC: 12% (95%CI:8%–16%) (p < 0.001); more frequent in females (42% vs 25%, p < 0.001) and tumors ≤ 4 cm (35.3% vs 23.3%, p = 0.0065). No association with outcome was found. In the SPLENDOUR trial (463 patients), the prevalence of membranous and cytoplasmic RANK positivity was 34% (95%CI:30%–38%) and 9% (95%CI:7%–12%), respectively, while prevalence for RANK-L was 5% (95%CI:3%–7%) and 36% (95%CI:31%–40%), respectively. Cytoplasmic RANK-L positivity was more common among females (47% vs 31%, p = 0.001) and in non-SCC histology (45% vs 10%, p < 0.0001). At the pre-specified 1% significance level, no prognostic or predictive effect was found. Conclusions: Both cohorts indicate that RANK expression is more common in adenocarcinoma/non-squamous NSCLC and in female patients. No prognostic effect is found, and in the clinical trial involving addition of denosumab to chemotherapy no predictive effect is detected.